Multiple endocrine neoplasia type 2 kindred with novel tandem RET mutations: Case report with an applied in silico mutational tolerance analysis. (15th February 2016) - Joshi, Rohan R.; Heineman, Thomas E.; Kutler, David I.; Cohen, Marc A.; Kuhel, William I.
Abstract: Background: The American Thyroid Association (ATA) has established guidelines for prophylactic thyroidectomy in multiple endocrine neoplasia type 2A (MEN2A) based on rearranged during transfection ( RET ) mutations. In silico analysis, which uses computer modeling to predict alterations in protein structure, is a new method for studying these mutations. Methods: We describe a kindred with MEN2A, all sharing a well‐documented RET mutation, p.C634Y, as well as a mutation of undetermined significance, p.I852M, which we analyzed via in silico analysis. Results: The p.C634Y mutation resulted in severe predicted RET alterations, whereas the p.I852M resulted in only modest changes. Both mutations together resulted in only a small additional disruptive effect in protein structure beyond that which occurred with p.C634Y alone. Conclusion: Although in silico analysis may be helpful in quantitating changes in protein structure that occur in patients who have novel RET mutations (single or multiple), additional factors must account for the highly variable aggressiveness of the disease (C‐cell hyperplasia/medullary thyroid carcinoma [MTC]) noted in our kindred. © 2016 Wiley Periodicals, Inc. Head Neck 38 : E1881–E1885, 2016